(untitled) (Journal of Medical & Health Sciences Review, 2025)
AIMS AND OBJECTIVES: To determine the effect of depression in adult patients suffering from low vision and the correlation of depression with low vision. METHOD: A cross-sectional study was performed on 86 subjects who visited the Low Vision Center at Mayo Hospital Lahore to determine the effect of depression in adults on functioning and daily life activities in low vision patients. All the patients were asked to fill out the questionnaire so that the extent to which the quality of life is affected can be measured. Qualitative data was analyzed through frequency and percentage. This study was conducted in February, March, April, and May 2022. RESULTS: This study revealed a high prevalence of depressive symptoms among 86 low vision patients. Notably, 50% felt bothered by minor things 1–2 days/week, and 30.2% reported poor appetite for 3–4 days/week. Feelings of sadness or inability to shake off a low mood were reported by 53.5% for 1–2 days and 24.4% for 3–4 days. Concentration problems affected 50% for 3–4 days, while 50% also reported feeling depressed some of the time, with 40.7% experiencing this for 3–4 days. A sense of effortfulness was noted in 58.1% for 1–2 days, and 50% thought their life had been a failure for 3–4 days. Despite this, 52.3% remained hopeful about the future most of the time. Other frequent symptoms included fearfulness (33.7% some of the time), sleep disturbance (44.2% none of the time, 37.2% some of the time), and loneliness (33.7% some of the time, 17.4% most of the time). These findings highlight a significant psychological burden among low vision patients, with many experiencing multiple depressive symptoms several days each week. CONCLUSION: There were high chances in low vision patients to develop depression because of visual loss, functional impairment, and difficulty in daily life activities. Visual impairment restricts a person’s independence and worsens the quality of life. During the study, it was possible to describe the specific indications of depression in each low vision individual. If a person is counseled properly, it is beneficial in increasing the functional performance and will also help them to avoid developing depression.